2007
DOI: 10.1096/fj.06-7491com
|View full text |Cite
|
Sign up to set email alerts
|

Moderate consumption of red wine (cabernet sauvignon) improves ischemia‐induced neovascularization in ApoE‐deficient mice: effect on endothelial progenitor cells and nitric oxide

Abstract: Moderate consumption of red wine is associated with a decreased incidence of cardiovascular diseases in populations with relatively high amount of fat in the diet. However, the mechanisms involved in this protective effect are not completely understood. Here we show that moderate consumption of red wine (equivalent to 2 glasses/day in humans) but not ethanol only, improves blood flow recovery by 32% after hindlimb ischemia in hypercholesterolemic ApoE-deficient mice. In ischemic tissues, red wine consumption r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 40 publications
(59 reference statements)
2
49
0
Order By: Relevance
“…We and others have previously shown that situations of excessive oxidative stress can impair VEGF-induced angiogenesis in endothelial cells. 17,18,25 Here we found that mature endothelial cells isolated from Nox2 Ϫ/Ϫ mice exhibit lower superoxide levels after CSE exposure. Moreover, reduced superoxide production in Nox2 Ϫ/Ϫ endothelial cells exposed to CSE was associated with improved cellular migration and tube formation in response to VEGF.…”
Section: And E Quantification Of Tube Formation (D) and Cellular Mmentioning
confidence: 64%
See 4 more Smart Citations
“…We and others have previously shown that situations of excessive oxidative stress can impair VEGF-induced angiogenesis in endothelial cells. 17,18,25 Here we found that mature endothelial cells isolated from Nox2 Ϫ/Ϫ mice exhibit lower superoxide levels after CSE exposure. Moreover, reduced superoxide production in Nox2 Ϫ/Ϫ endothelial cells exposed to CSE was associated with improved cellular migration and tube formation in response to VEGF.…”
Section: And E Quantification Of Tube Formation (D) and Cellular Mmentioning
confidence: 64%
“…14 To evaluate local oxidative stress levels in ischemic muscles, nitrotyrosine immunostaining (Upstate) and dihydroethidium staining (DHE, Molecular Probes) were used. 25 …”
Section: Immunochemistrymentioning
confidence: 99%
See 3 more Smart Citations